Comparison of radiographic and clinical diagnosis of approximal and occlusal dental caries in a young adult population - Hopcraft MS, Morgan MV. (Blackwell Synergy, 2005)
The aims of the study were: (1) to determine if bitewing radiographs provided additional diagnostic yield for occlusal and approximal dental caries in adults aged between 17 and 30 years of age when compared with a clinical examination only, (2) how this translated into the measurement of dental caries experience, and (3) to determine the influence of water fluoridation on the diagnosis of dental caries in occlusal and approximal surfaces by clinical examination alone and by radiographic examination.